Analisis Kinerja Petugas Farmasi Pelayanan Obat Pasien Rawat Jalan Di RSUD dr.R.Soedjati Soemodiardjo Purwodadi - Grobogan - Christine Diah Wahyuningsih; Susilo Endrawanti (Serat Acitya, 2017)
With the rising status of the community's economy, ease of communication and increasing knowledge about health causes people demand better quality health care, both in terms of attitude and behavior of officers. In accordance with Undang-Undang No. 77 |Tahun 2015 Tentang Pedoman Organisasi Rumah Sakit (Guidelines for the Organization's Hospital), the hospital must perform some functions which aims to realize a hospital organization that is effective, efficient, and accountable in order to achieve the vision and mission of the hospital in accordance with the Good Corporate Governance and Good Clinical Governance. In connection with the above description, researchers interested in conducting research titled "Influence of Pharmaceutical Officer Performance Against Drugs Service Satisfaction Level on Hospital Outpatient dr.R.Soedjati Soemodiardjo Purwodadi". The formulation of the problem in this research is "Is There a clerk Performance Influence Satisfaction Against Pharmaceutical Drug Outpatient Services in dr. R. Soedjati Soemodiardjo Purwodadi? ". The type of research used in this study is explanatory type one. The main instrument in this study were respondents consisting of all visitors Outpatient Pharmacy dr. R. Soedjati Soemodiardjo Purwodadi visiting at the time of study cunducted (50 respondents). Locus of the study is dr.Soedjati Soemodiardjo Hospital Purwodadi Grobogan. This study focused on the effect of worker performance and satisfaction levels outpatient drug services. Data collection techniques by observation, questionnaires, interviews, and literature. Data processing techniques include: editing, coding, and tabulating, To complement the quantitative analysis used qualitative analysis with percentage analysis measurement scale formula. Value = (Score achieved) / (Score expected) × 100%, with the result of the value for the variable X = 70.8% included in the interval 50% - 74.99%, so as to be in the medium category. While the variable Y with the results of value = 71.1% is in the interval 50% - 74.99%, resulting in medium category. As well as testing the hypothesis by using Product Moment Correlation to the relationship variables X and Y obtained price r xy = 0.62, N = 50 Γtable with the significant level of 5% value was 0.273. Thus it can be argued that the value Γobtained is greater than the Γtable (0.62>0.273), so that the statement "There is Influence Officer Performance Against Pharmaceutical Drug Services Patient Satisfaction in Outpatient Hospital Pharmacy dr.R.Soedjati Soemodiarjo Purwodadi" is ACCEPTED. Suggestions can be submitted by researchers are the addition of patient waiting chairs, waiting room cooling equipment, their training for pharmacist, and doctor's clock settings